Of Maps, Libraries, and Lectures: The Nebenzahl Lectures, the Hermon Dunlap Smith Center, and the Study of Map History. Issue 2 (2nd September 2021) - Edney, Matthew H.
Abstract: The Nebenzahl Lectures, held triennially at the Newberry Library, Chicago, since 1966, have been crucially important in the development of sociocultural map studies. This essay explores their creation within the context of the challenges facing the Newberry in the 1960s, with special attention to the role of Ken and Jossy Nebenzahl; it then examines the significance of R. A. Skelton's inaugural lectures and the subsequent history and influence of the lectures, before revisiting Skelton's vision for the field and its continuing paucity of institutional support. Skelton's lectures had two major consequences: they led to the formation in 1972 of the Newberry's Hermon Dunlap Smith Center for the History of Cartography; and his conception of the history of cartography as an intellectually relevant and autonomous discipline was soon proselytized by J. B. Harley and David Woodward as the necessary foundation for a new approach to maps as cultural documents and social instruments.